O ensino de processos de separação de misturas por meio de análise dos livros didáticos e uso de atividades experimentais investigativas - Friggi, Daniela do Amaral (2016)
Conducting contextualized experimental activities in chemistry teaching has been advocated by several authors as a mediator teaching tool in learning process. The key content of mixtures separation processes in chemistry teaching is little explored in carrying out experimental activities in high school due to the fact that schools often do not have science laboratories, although such content is present in a wide range of students' everyday situations. The following study aimed to investigate the use of contextualized investigative experimental activities for the study of mixtures separation processes, providing students with a better understanding and learning in relation to mixture separation processes and other concepts related to the content approached. Data collection was carried out into three stages, the first stage was through the analysis of chemistry textbooks of the first year of high school for a meaningful profile that students could have on mixtures separation processes. The second stage was a survey with three open questions to verify the concepts of students on mixtures separation processes. And at the last stage, the experimental activities from investigative situations - contextualized problems, which kept a logbook and recordings to record observations, interesting speeches of the students and the implementation of activities were carried out. It was found that the textbooks are improving and that the three items analyzed: context, images, and exercises are significant modifications to assist teachers and students in teaching and learning the content of mixtures separation processes. Overall, from the previous conceptions of the students on the mixtures separation processes, it was found that the students have knowledge of the content, but have difficulties in relating the most suitable separation process for a given mixture, which is not present in their daily lives. After carrying out the experimental investigative contextualized activities, it was observed that from their previous knowledge allied with the activities, students improved existing concepts, acquired new knowledge and learned new ways to understand the content of study. Moreover, to develop the experimental activities proposed, the students had to use alternative materials. Thus, the lack of materials and equipment did not prevent the accomplishment of the activities. Thus, it can be said that the use of contextualized investigative experimental activities, besides motivating students, has contributed to the learning and understanding of mixtures separation processes.